2019
DOI: 10.1136/bcr-2019-232093
|View full text |Cite
|
Sign up to set email alerts
|

Oral sarcoidosis aiding in diagnosis of underlying systemic disease

Abstract: Sarcoidosis is a chronic, multisystemic, granulomatous disease of unknown aetiology characterised by the formation of non-caseating granuloma. It shows slight female predominance and has a bimodal age distribution. Lungs, skin, eye and liver are commonly affected. The oral lesion, though uncommon, may present as submucosal nodule, papule or superficial ulceration. Occasionally, oral lesion may be the first manifestation of underlying systemic disease. This case is interesting because it emphasises that dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Nevertheless, studies have shown that oral sarcoidosis may be accompanied by more severe systematic involvement, 19 and close follow‐up is recommended. We hope to bring awareness, to other dentists and fellow researchers, toward the oral signs and symptoms of sarcoidosis, features that are commonly assumed to be unimportant or irrelevant to the greater course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies have shown that oral sarcoidosis may be accompanied by more severe systematic involvement, 19 and close follow‐up is recommended. We hope to bring awareness, to other dentists and fellow researchers, toward the oral signs and symptoms of sarcoidosis, features that are commonly assumed to be unimportant or irrelevant to the greater course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, studies have shown that oral sarcoidosis can be a manifestation of a systematic disorder (18), therefore follow-up of the patient in this stage is necessary. We hope to bring awareness to other dentists and fellow researchers to notice the oral symptoms of sarcoidosis which is usually assumed to be irrelevant to the disease.…”
Section: Discussionmentioning
confidence: 99%